To complete the polynomial division \( (3x^4 + 9x^2 - 13) \div (x^2 - 5x) \), we will perform long division step by step.
-
Divide the leading term: \( \frac{3x^4}{x^2} = 3x^2 \)
-
Multiply \( 3x^2 \) by \( (x^2 - 5x) \): \[ 3x^2 \cdot (x^2 - 5x) = 3x^4 - 15x^3 \]
-
Subtract: \[ (3x^4 + 9x^2 - 13) - (3x^4 - 15x^3) = 15x^3 + 9x^2 - 13 \]
-
Repeat the process: Divide the leading term: \( \frac{15x^3}{x^2} = 15x \)
-
Multiply: \[ 15x \cdot (x^2 - 5x) = 15x^3 - 75x^2 \]
-
Subtract: \[ (15x^3 + 9x^2 - 13) - (15x^3 - 75x^2) = 84x^2 - 13 \]
-
Repeat the process: Divide the leading term: \( \frac{84x^2}{x^2} = 84 \)
-
Multiply: \[ 84 \cdot (x^2 - 5x) = 84x^2 - 420x \]
-
Subtract: \[ (84x^2 - 13) - (84x^2 - 420x) = 420x - 13 \]
At this point, the degree of the remainder \( (420x - 13) \) is less than the degree of the divisor \( (x^2 - 5x) \), which means we cannot divide anymore.
Therefore, the final result of the division is: \[ \text{Quotient} = 3x^2 + 15x + 84 \] \[ \text{Remainder} = 420x - 13 \]
Given the options provided, the correct response is: The remainder is \( 420x - 13 \).